Development and validation of a sensitive immunoassay for the skeletal muscle isoform of creatine kinase - Lo, K. R.; Hurst, S. M.; Atkinson, K. R.; Vandenbogaerde, T.; Beaven, C. M.; Ingram, J. R. (Journal of Science and Medicine in Sport, 2010)
Creatine kinase (CK) is a marker of muscle damage and pathology present as multiple tissue-specific circulating isoforms. CK is often measured using enzyme activity assays that are unable to distinguish these isoforms. We have developed an immunoassay specific for the MM isoform of CK, found predominantly in skeletal muscle, which uses very small volumes of plasma (1-2 [mu]L). A sandwich enzyme-linked immunosorbent assay (ELISA) for CK-MM was developed using isoform-specific antibodies. Cross-reactivity with CK-BB and MB isoforms was also assessed. The ELISA was validated using plasma samples from a group of athletes, and the measured CK-MM concentrations were correlated with CK enzyme activity assays measured by a contractor using the same samples. The CK-MM ELISA has a limit of detection of 0.02 ng/mL, an IC50 of 2.3 ng/mL, and 5.8% cross-reactivity with CK-MB. CK-MM concentrations measured using this assay correlate well (p < 0.0001, Spearman r = 0.89) with enzyme activity assays. The CK-MM-specific ELISA can be used to help assess skeletal muscle damage independent of enzyme activity or interference from other CK isoforms, leading to more precise studies of muscle biology.